A Persistent Place for Hunter-Gatherers During the Late Holocene: The Case of Burials in Pit on the Coast of Lángara Bay, Argentine Patagonia. (3rd July 2018) - Zilio, Leandro; Hammond, Heidi
ABSTRACT: In Argentine Patagonia, the type of archaeological burial "in pit" has been only identified on the coast of Lángara Bay. This modality is characterized by the presence of single and multiple primary burials. Studies on five human burials in pits are presented in this article. The aim is to compare the contexts of burials in pit at the site level and the spatial characteristics of their distribution in the Lángara Bay locality from a diachronic perspective. The approach focuses on mortuary practices and social relations of hunter-gatherer groups during the Late Holocene. A characterization of the burials, their chronologies, bioarchaeological determinations, stable isotope studies, and their spatial distribution are included. The results allow us to chronologically place the contexts between ca. 3000 and 2000 cal BP. A spatial pattern in the distribution of burials in the coastal landscape was identified. Finally, it is proposed that this part of the Patagonian coast was a persistent place of burials in pit.